Community treatment orders: towards a new research agenda. (June 2018) - Brophy, Lisa; Edan, Vrinda; Gooding, Piers; McSherry, Bernadette; Burkett, Tatum; Carey, Sue; Carroll, Andrew; Callaghan, Sascha; Finch, Anne; Hansford, Margaret; Hanson, Sarah; Kisely, Steven; et al.
Objectives: The aim of this study was to report on a half-day multi-stakeholder symposium on community treatment orders (CTOs) hosted by the Melbourne Social Equity Institute (MSEI), which identified research gaps and opportunities, and produced an agreed agenda for future CTO research. Methods: The MSEI convened a symposium for 22 experts in CTO research to discuss research priorities in this field in Australasia. An independent moderator elicited views and recommendations and produced a report detailing possible research projects. Results: Research on CTOs is contentious and there is a need to gather and examine information regarding both their use and utility. Due to the complexities involved, it was agreed that research should be undertaken in partnership with persons with had lived experience of mental health problems, clinicians, policymakers and other interdisciplinary stakeholders. Five key areas for future investigation were identified. Conclusions: The issues and recommendations arising from the symposium should shape the scope, nature and conduct of future research directions in the field.